2006
DOI: 10.1158/0008-5472.can-06-1722
|View full text |Cite
|
Sign up to set email alerts
|

Asynchronous Growth of Prostate Cancer Is Reflected by Circulating Tumor Cells Delivered from Distinct, Even Small Foci, Harboring Loss of Heterozygosity of the PTEN Gene

Abstract: The clinical value of prostate-specific antigen (PSA)-positive circulating tumor cells (CTCs) is still a matter of debate and it is also still unclear if these CTCs actually represent the primary tumor. Therefore, we isolated PSA-positive CTCs from the peripheral blood of patients suffering from multifocal cancers and did genetic profiling of each cancer focus by a multiplex PCR-based microsatellite analysis (D7S522, D8S522, NEFL, D10S541, D13S153, D16S400, D16S402, D16S422, and D17S855). In 17 of 20 prostate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
48
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 14 publications
5
48
0
Order By: Relevance
“…Thus, they hypothesized that the index tumour may not always be representative of the pathological stage. Similarly, other investigators observed that even small foci, down to 0.2 cm 3 in size, may show a significant release of tumour cells into the bloodstream 26 and can lead to lymph node metastasis. 27 As Miller and Cygan 10 pointed out, tumours need not acquire a large volume before they become locally invasive.…”
Section: Discussionmentioning
confidence: 57%
“…Thus, they hypothesized that the index tumour may not always be representative of the pathological stage. Similarly, other investigators observed that even small foci, down to 0.2 cm 3 in size, may show a significant release of tumour cells into the bloodstream 26 and can lead to lymph node metastasis. 27 As Miller and Cygan 10 pointed out, tumours need not acquire a large volume before they become locally invasive.…”
Section: Discussionmentioning
confidence: 57%
“…2, 3). One advantage of immunocytochemical methods is the opportunity to include morphologic criteria and to further characterize individual cells by additional antibodies, fluorescence in situ hybridization technology, or molecular methods after detection (22,23).…”
Section: Discussionmentioning
confidence: 99%
“…Besides the concordance of tumour-related LOH on cell-free DNA in blood with LOH on DNA from matched primary tumour tissues, discrepancies have also been found (Fleischhacker & Schmidt, 2007). These contradictory LOH data derived from blood and tumour tissue and the low incidence of LOH on cell-free DNA have been explained in part by technical problems and the dilution of tumour-associated cell-free DNA in blood by DNA released from normal cells Schmidt et al, 2006). Moreover, abnormal proliferation of benign cells, due to inflammation or tissue repair processes, also leads to an increase in apoptotic cell death, the accumulation of small, fragmented DNA in blood and the masking of LOH (Schulte-Hermann et al, 1995).…”
Section: Genetic Analyses Of Cell-free Dnamentioning
confidence: 99%
“…Deletions in the BRCA1 gene have recently been implicated in metastatic spread and tumour progression in prostate cancer (Bednarz et al, 2010). A comparative genetic profiling of isolated PSA-positive CTCs and multifocal prostate tumour tissues was performed by Schmidt et al They showed that the detection of LOH at the BRCA1 locus in CTCs and primary tumours was associated with an early biochemical recurrence (Schmidt et al, 2006). In a recent study, Okegawa et al determined for the first time the relation between CTCs detected on the CellSearch System and circulating tumour-related methylated DNA using a sensitive SYBR green methylation-specific PCR (Okegawa et al, 2010).…”
Section: Cell-free Tumour Dna As a Marker For Circulating Tumour Cellsmentioning
confidence: 99%